Investigation of thermal techniques to mitigate buckling distortion in welding panels - Nagy, T. (Cranfield University, 2012)
This thesis describes the advancements of the application of thermal tensioning techniques to different weld geometries in order to eliminate buckling distortion. The main goal of this work is to better understand these techniques through experimental and numerical investigation and increase their technological maturity to aid industrial implementation. The thermal tensioning techniques investigated in this work are Thermal Tensioning by Cooling and Thermal Tensioning by Heating. The investigation for both techniques encompasses thermal source characterisation, application to different weld geometries and residual stress measurements and analysis of both butt and fillet welded samples. A detailed technology transfer study of Thermal Tensioning by Cooling was carried out in which different aspects of the application of TTC to arc welding (Gas Metal Arc Welding and Gas Tungsten Arc Welding) was examined. This study focused on the influence of both the liquid CO2 delivery system installation and welding tooling and jigging on the effectiveness of Thermal Tensioning by Cooling in reducing buckling distortion. Experimental and numerical cooling source characterisation was also carried out in the Thermal Tensioning by Cooling work to investigate the characteristics of the cooling source under different cooling conditions. The Thermal Tensioning by Cooling work was then concluded with welding trials and residual stress measurement and analysis. The results of the Thermal Tensioning by Cooling study show that the installation of the liquid CO2 delivery system as well as the welding tooling and jigging has a major influence on the effectiveness of Thermal Tensioning by Cooling in reducing buckling distortion. The cooling source characterisation work reveals that the most important parameter of the cryogenic nozzle delivery system used in this work is the Air Entrainment Gap. A description of a control system of Thermal Tensioning by Cooling is suggested based on controlling the Air Entrainment Gap. The residual stress analysis shows a reduction in the Applied Weld Load and minor changes in the tensile peak of the residual stress distribution of both butt and fillet welded panels. The Thermal Tensioning by Heating investigation includes heat source characterisation, application of Thermal Tensioning by Heating on butt and fillet welds, utilisation of alternative heat sources and residual stress analysis. The results of these investigation show that Thermal Tensioning by Heating is also highly effective in eliminating buckling distortion in butt, fillet and overlapped panels. The applied heating temperature in this work is typically in the range of 160-250 °C but not greater than 330 °C. The residual stress measurements reveal that the additional heating of Thermal Tensioning by Heating generates a positive stress gradient at the location of heating.